Rhizome extracts of Acorus odoratus: Antifungal, anti-yeast, anti-oxidant and HPLC quantification - Khan, Bilal Muhammad; Bakht, Jehan; Khan, Wajid (Bangladesh Journal of Pharmacology, 2017)
Different extracts from the rhizomes of Acorus odoratus were assessed for the presence of antifungal, anti-yeast and anti-oxidant potential. Mild antifungal and robust anti-yeast potential were revealed by the tested samples. A gigantic anti-oxidant activity, however, was noted for all extracts at each concentration used. The data further revealed that n-butanol and ethyl acetate fractions measured fair antifungal (41.5% inhibition against Rhizopus oryzae and 36.2% inhibition against Acremonium alternatum at 2000 µg/well respectively), and highest anti-yeast (70.3 and 66.8% activities respectively at 2000 µg/disc) and anti-oxidant (95.8 and 97.9% activities respectively at 250 ppm) potential while samples extracted with water were least potent. Furthermore, both n-butanol and ethyl acetate were found as the best extraction solvents for antifungal, anti-yeast and anti-oxidant compounds (particularly gallic acid) from the rhizomes of A. odoratus in HPLC analysis. Video Clip of Methodology HPLC: 3 min 48 sec Full Screen Alternate